2020
DOI: 10.1007/s11192-020-03546-x
|View full text |Cite
|
Sign up to set email alerts
|

Do journals flipping to gold open access show an OA citation or publication advantage?

Abstract: The effects of Open Access (OA) upon journal performance are investigated. The key research question holds: How does the citation impact and publication output of journals switching ("flipping") from non-OA to Gold-OA develop after their switch to Gold-OA? A review is given of the literature, with an emphasis on studies dealing with flipping journals. Two study sets with 119 and 100 flipping journals, derived from two different OA data sources (DOAJ and OAD), are compared with two control groups, one based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 23 publications
3
22
0
2
Order By: Relevance
“…We have presented one of few studies on journals which flipped from a CA to an OA model and its effect on journal publication volumes, article-and journal-level citations metrics and how these compare to journals which still pursue the CA model. The literature reporting studies on flipped journals shows that journals' IFs usually increase after flipping (Bautista-Puig et al, 2020;Busch, 2014a). Our results agree with these previous findings, but show that whilst IF and ARC increase generally in the years following flipping, they vary greatly across scientific fields.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have presented one of few studies on journals which flipped from a CA to an OA model and its effect on journal publication volumes, article-and journal-level citations metrics and how these compare to journals which still pursue the CA model. The literature reporting studies on flipped journals shows that journals' IFs usually increase after flipping (Bautista-Puig et al, 2020;Busch, 2014a). Our results agree with these previous findings, but show that whilst IF and ARC increase generally in the years following flipping, they vary greatly across scientific fields.…”
Section: Discussionmentioning
confidence: 99%
“…Note that journal metadata in DOAJ is provided by the publishers directly and is thus not "verified" by any third party. As Sotudeh and Horri (2007) and Bautista-Puig et al (2020) have shown this can often lead to inaccurate data, e.g., in terms of flipping date. To build a group of flipped journals, we extracted details of all journals in DOAJ as well as the flipping year.…”
Section: Groups Of Flipped Journalsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, citations to articles tend to increase (Archambault et al, 2016) and, as a consequence, so does impact measured with journal-level metrics (Momeni et al, 2021). 20 Another positive consequence is that the number of articles by authors from low-and middle-income countries increases (Bautista-Puig et al, 2020). Integrating altmetric indicators into published articles would help scholars to easily obtain document-level metrics.…”
Section: Open Research Evaluationmentioning
confidence: 99%